KEEFEKTIFAN STRATEGI PREVIEW, QUESTION, READ, SUMMARIZE AND TEST (PQRST) MENGGUNAKAN PICTURE STRIP STORY PADA PEMBELAJARAN READING - Pralita Imas Mardhika; Ida Ayu Panuntun (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
English as an international language is used by all people in all cauntries. Based on the result of the observation to the English teacher of SMP N 4 Batang, there were so many students who had difficulties in reading comprehension of Descriptive text. The students got lack of vocabulary. This study was aimed to know the effectiveness of strategy Preview, Question, Read, Summarize and Test (PQRST) assisted by Picture Strip Story in reading comprehension of Descriptive text. The method used in this study was experimental study. The total sample in this research was 66 students  who  were  divided  into  two  group.  Control  group  consisted  of  33  students  and experimental group consisted of 33 students. The finding can be seen in the comparation between the mean score of pre test and post test in control group and experiment one. The writer found that the mean of pre-test was 63.636 and the mean of post-test was 74.848. It means that there was effect by looking at increasing the average score. In other words, the mean of pre-test and also post-test showed a significant improvement. for the control group, the mean score of pre-test was63.030 and the post-test was 65.909. The result of this group was less than the experimental group. It also be  proven by T Test of post test was 3.326. It means that t test was higher that t-table (1.666). It can be concluded that teaching learning process of reading comprehension of Descriptive text using PQRST strategy assisted by Picture Strip Story was effective. It is suggested that the finding can be the contribution in teaching learning process of reading comprehension. It is one of the media that can be used to teach reading. It can motivate the students when studying ina group.